PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI KELAS XI SMA MUHAMMADIYAH 1 PEKANBARU - Amaliah, Fitri Rezki; Darmawati, Darmawati; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to improve the ability of creative thinking and learning outcomes of XI MIA 3 students in Muhammadiyah 1 Pekanbaru High School with a guided inquiry model. This research is a Classroom Action Research (CAR) conducted in two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The research subjects were students of class XI MIA 3 in Muhammadiyah 1 High School Pekanbaru, totaling 31 students consisting of 11 men and 20 women. The parameters measured are the ability to think creatively and student learning outcomes consisting of cognitive, affective and psychomotor abilities of students. Data collection techniques were carried out by tests (LKPD, Post test and daily test) and non-test (observation sheet). Data analysis techniques are carried out quantitatively and supported by descriptive analysis techniques. The results showed that the average creative thinking ability of students in the first cycle was 76.51 with the Enough category and increased in the second cycle to 85.40 with the Good category. The average value of absorption of students in the first cycle was 80.50 with the category Enough and increased in the second cycle to 87.51 with the Good category. For student learning completeness in learning cycle I which is equal to 87.09% and cycle II has reached 100% complete. While for the average value of attitudes of students in learning cycle I is 82.74 with the Enough category and increases in the second cycle to 89.45 with the Good category. The average psychomotor value of students in learning cycle I is 83.36 with the category Enough and increases in the second cycle to 90.59 with the Good category. Based on the results of the study it can be concluded that the Guided Inquiry model can improve creative thinking skills and learning outcomes of XI MIA 3 students at Muhammadiyah 1 High School Pekanbaru.Key Words: Guided Inquiry, Creative Thinking, Learning Outcomes